A review of potential analgesic effect, chemical components, toxicology and detoxification of Duanchangcao - Ruoyue Huang; Cuishan Zhang; Yan Cheng; Binbin Zhang; Fei Li (Pharmacological Research - Modern Chinese Medicine)
Introduction: Duanchangcao, a common term in traditional Chinese medicine with high frequency, including about 40 kinds of medicinal plants distributed all over China. They have the pharmacological effects, including dispelling wind, eliminating dampness, reducing oedema, and relieving pain. Aim of the review: This study aims to review the analgesic and toxicological effects, including clinical adverse reactions, toxic chemical compounds and mechanisms. Methods: The relevant analgesic and toxicological reports of five major medicinal plants were collected from various academic databases and search engines, including Google, Google Scholar, PubMed, Web of Science, CNKI and Wanfang. Results: The clinical side effects of Duanchangcao have been recorded in numerous studies in China. They exhibit the side effects on different organs. At least 63 isolated chemical compounds have been reported to show toxic effects and mainly are alkaloids, flavones, diterpenes and triterpenes. The toxic mechanisms of Duanchangcao are associated with apoptosis, autophagy, immunological injury, oxidative stress and metabolism. The use of new technologies and proper processing can ensurre safe application. One typical clinical use has been developed as an analgesic drug, which benefits patients' physical and mental health, and improve the quality of life. Discussion: Duanchangcao, a series of medicines used in China for several centuries, has been found to possess biological activities. To appropriately utilize Duanchangcao as an analgesic in clinical practice, the changed pathways and mechanisms of toxicity following the exposure need to be clarified, and the preventive approaches should be further studied. Additionally, drug-drug interaction still remain to be a challenge during their applications.